Pengaruh relationship marketing terhadap loyalitas konsumen pada Rumah Makan Patene di Makassar - Lisa Jolanda Catherine Polimpung (Jurnal Manajemen Maranatha, 2020)
Currently the world has entered globalization where this has led to many changes that have occurred in the aspect of life where competition in the industrial world is also getting tougher. Patene Restaurant in Makassar is a restaurant where you can feel the competition that is happening in the world today. This study analyzes the effect of relationship marketing input, namely understanding customer expectations, building service partnerships, and total quality management on the loyalty of consumers at Patene Restaurant in Makassar. The number of respondents was 211 respondents where the respondents filled out the questionnaire distributed by the researcher. This study found that the relationship marketing input applied by Patene Restaurant in Makassar has a significant effect on consumer loyalty at Patene Restaurant.